Antimicrobial properties of traditional kefir: An in vitro screening for antagonistic effect on Salmonella Typhimurium and Salmonella Arizonae. (January 2022) - Gut, Abraham Majak; Vasiljevic, Todor; Yeager, Thomas; Donkor, Osaana N.
Abstract: The rise of antibiotic resistance in Salmonella has necessitated the need for alternative ways of preventing and controlling infections. Fermented products have been recognised to have prophylactic and therapeutic properties against diseases. This study focused on the analysis of antagonistic effect of two different traditional kefir grains on Salmonella Arizonae and Salmonella Typhimurium after 24 and 48 h fermentation. Kefir supernatants were analysed for ethanol, organic acid and protein composition using gas chromatography, high performance liquid chromatography and shotgun proteomics, respectively. Salmonellae were rapidly eradicated in kefir possibly due to action of lactic acid as kefir cell-free supernatant contained high concentrations of lactic acid ranging from 83.59 to 229.92 mm . Other molecules with recognised antibacterial activities including carbonyl compounds, histone and cathelicidin were detected in the soluble phase that could have provided synergistic effect with the organic acids.